Order book, order flow and returns: evidence from the Brazilian stock exchange - Alexandre, Michel; Ferreira, Fernando Fagundes; Rodrigues Neto, Camilo (Redeca, Revista Eletrônica do Departamento de Ciências Contábeis & Departamento de Atuária e Métodos Quantitativos, 2018)
The purpose of this study is to analyze the stylized facts of the order book of stocks traded in the São Paulo Stock Exchange (BOVESPA), as well as of the returns engendered by the order book dynamics. We used data from June 2006 to January 2009 regarding a sample composed by the twenty most traded stocks in BOVESPA. The empirical results corroborated some stylized facts observed in stocks of other countries, but refuted others.